Somatic Care Performances: Turtle Disco and Tendings - Kuppers, Petra; Watkin, Jessica; Preston, VK; Changfoot, Nadine; Hartblay, Cassandra; Gold, Becky (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2025)
This essay discusses accessibility, community, bodily pain, and writing engagement, as well as meanings of “dramaturgy” in somatic and improvisation contexts. We work together as tender bodymindspirits—never just one, always interwoven—in complex inner and outer worlds. As a group of people working together, we use writing to find paths for witnessing experience. We created performances for and with each other. These are all small practices, often enacted in public, but not through spectacular performance. Instead, our work here draws on specific networks nourished through friendship and community—in the first case, the local circle of a small town in Michigan; in the second, the circle of disability-interested scholars in the Canadian East.Plain language abstract (adapted by Kelsie Acton with Daniel Foulds)This is writing aboutI’m Petra Kuppers, the main writer. I think about my own pain and making art when life is full of pain. I think about dramaturgy in caring for one another and moving together. Dramaturgy is a way of making meaning and making people feel. There are also two groups of artists in this essay. These two groups of artists share stories about making art together. I don’t write about the artists’ stories. I just share them so you can feel and think about making art together. The first set of stories is about a group of disabled people who met in Ypsilanti, Michigan, USA. Many people in this group live with pain. The second set of stories is about artists who work in universities. The artists meet in Toronto, Canada. We use movement, sound, and thinking deeply to make art about